Examination of Lower and Upper Extremity Isokinetic Strength Parameters and Speed Performance of Water Polo Athletes - Ebru Özer; Recep Soslu (Selcuk University, 2021)
Abstract The aim of this study is to examine the relationship between the isokinetic lower and upper extremity parameters and speed performance of water polo athletes aged 15-17. Ten elite male water polo players, aged 15-17, voluntarily took part in the study. Right and left shoulder internal / external rotator, right and left knee flexion/extension isokinetic force measurements (60° sec-1 and 180° sec-1) and 25m swimming speed measurements were measured. Linear regression analysis was used to analyze the data, p lt;0.05 was taken as a significance level. As a result of the analysis of the obtained data, between 25m and 60° right and 60° left knee extension and knee flexion values (F (4,9) = .51, p gt; .05, R2 = -. 28) and 180° right and left knee extension and knee flexion, there was no statistically significant difference (F (4,9) = 1.26, p gt; .05, R2 = .50). Furthermore, no statistically significant difference was found between the external and internal rotation values of 25m and 60 ° right and left shoulder and external and internal rotation of the right and left shoulders 180 ° (F (4.9) = 2.63, p gt; .05, R2 = .68). As a result, it is thought that the major force that draws the fluid during swimming is provided by the arm and shoulder muscles, while the leg muscles play a supporting role. In addition, it is thought that water polo players' body, arm and shoulder muscles need higher energy and force requirements during swimming than pelvic and leg muscles are an important factor for performance. Therefore, it is supported by the view that the upper extremity muscles of elite water polo players can be trained at a higher level than lower extremity muscles. Keywords:Force, Isokinetic strength, Speed, Water polo.